Psychological Foundations of the Love Curriculum in Humanistic Education - Cucum Novianti; Jajat Darojat; Arif Rahman Hakim (Islamic Counseling and Parenting Journal, 2026)
This study aims to analyze the psychological approach in the love curriculum from the perspective of humanistic education. The study is motivated by a research gap indicating that contemporary educational practices are still predominantly oriented toward academic and cognitive achievements, while the affective, emotional, and relational dimensions of learners have not received adequate attention. As a result, various issues such as declining empathy, intolerance, bullying, and weak interpersonal relationships within educational settings have become increasingly prevalent. This study employs a qualitative approach using library research. Data were collected from books, scientific journal articles, and other relevant literature related to educational psychology, humanistic education, and the love curriculum. Data were analyzed through content analysis, including data reduction, data presentation, and conclusion drawing. The findings reveal that the love curriculum is an educational paradigm that places compassion, empathy, respect for human dignity, and healthy interpersonal relationships as the foundation of the learning process. The novelty of this study lies in the integration of psychological approaches with the concept of the love curriculum within a humanistic education framework as a model for strengthening students’ affective development. Theoretically, this study enriches the discourse on humanistic education by providing a psychological perspective that emphasizes the importance of emotional needs in the learning process. Educationally, the findings imply the need to develop emotionally safe learning environments, empathetic teacher–student relationships, and dialogic and participatory learning practices to support character development, emotional intelligence, and humanitarian values among students.